The Characteristics of Air Quality Changes in Hohhot City in China and their Relationship with Meteorological and Socio-economic Factors - Qingchun Guo; Zhenfang He; Zhaosheng Wang (Aerosol and Air Quality Research)
Abstract Air pollution affects sustainable development of the natural environment and social economy. In this article, the changes in air quality index (AQI) and six air pollutants in Hohhot during 2014–2022 are analyzed. The results imply that the annual average concentrations of five air pollutants (SO2, PM10, PM2.5, NO2, and CO) and AQI values declined year by year over 2014–2022. Compared with 2014, AQI in Hohhot fell by 22.5% in 2022. However, the annual average concentrations of O3 increased year by year. PM2.5 and PM10 were the major factors in influencing AQI. Among the five types of atmospheric pollutants, the relationship between NO2 and O3 is strongest, implying that NO2 plays a significant influence in the formation of O3 and PM2.5. Meteorological and socio-economic factors have a significant impact on air quality. The average wind speed (AWS), average pressure (AP), sulfur dioxide emissions (SOE), nitrogen oxide emissions (NOE), and particulate matter emissions (PME) have a positive effect on changes in air quality. The results provide the information of great importance for the management of air quality in Hohhot City.